Rehydroxylation of Fired‐Clay Ceramics: Factors Affecting Early‐Stage Mass Gain in Dating Experiments. (26th May 2013) - Wilson, M. A.; Clelland, S.; Carter, M. A.; Ince, C.; Hall, C.; Hamilton, A.; Batt, C. M.
<x xml:space="preserve">Abstract</x> To obtain accurate results in the RHX dating of ceramics, it is essential that the RHX measurements are continued until the rate of mass gain is constant with (time)1/4. In this paper, we discuss how the initial stages of mass gain are affected by the specific surface area (SSA) of the ceramic material. The paper provides guidance on experimental protocols to avoid dating results being distorted by relatively early‐time mass gain data.